Design and synthesis of myo-inositol (1,4,5)-trisphosphate receptor antagonists - Ye, Y (2013)
Well-regulated Ca2+ signalling is essential for every living organism, and disruption of this signalling can lead to diseases including heart failure, neurological disorders and diabetes. Intracellular Ca2+ levels are regulated by influx of extracellular Ca2+ through channels located in the cell membrane. In addition, release of Ca2+ from intracellular stores also plays an important role in controlling intracellular Ca2+ concentration. Of the three types of intracellular Ca2+ stores that have been characterised those with D-myo-Inositol 1,4,5 trisphosphate receptors (InsP3 Rs) showed a close relationship with cell proliferation. Hence, selective blockage of InsP3 Rs will allow better understanding of Ca2+ signalling and might also unveil novel treatment for cancers, in the long term. There were no selective InsP3 Rs antagonists known at the start of these studies. Based on the crystal structure of InsP3 Rs bound to InsP3 and SAR studies of InsP3, we designed and tested several InsP3 analogues. Compound 15, 16 and 23 acted as InsP3 R antagonists, though their selectivity for InsP3 Rs was not completely determined. Furthermore, we also attempted to improve the potency of 16 via substitution at the 1-postion phosphate. By considering the interaction formed between adenophosphostins and InsP3 Rs compounds (53-55) were designed and synthesised. In addition, analogues of compound 92, selected from an in silico screen, have led to the discovery of another novel scaffold that acts as an InsP3 R antagonist.